Using the Malthus programme to predict the recruitment of patients to MR-linac research trials in prostate and lung cancer. Issue 1 (January 2017) - Sanderson, Benjamin; McWilliam, Alan; Faivre-Finn, Corinne; Kirkby, Norman Francis; Jena, Rajesh; Mee, Thomas; Choudhury, Ananya
Summary: In this study, we used evidence-based mathematical modelling to predict the patient cohort for MR-linac to assess its feasibility in a time of austerity. We discuss our results and the implications of evidence-based radiotherapy demand modelling tools such as Malthus on the implementation of new technology and value-based healthcare.